Uso de rocha carbonática e microrganismos como suprimento alternativo de fósforo - Richardi, Mayco Mascarello (2022)
Phosphorus (P) fixation reaction in Latosols is among the main economic limitations for tropical agriculture, as they require high amounts of this element by crops. As P sources are exhaustible and this is an essential element for plants, it is extremely important to seek sustainable and efficient alternatives in its use. The objective of this work was to evaluate the alternative supply of P for the initial development of the corn crop, with the application of carbonatite rock powder (PR) combined with reduced proportions of simple superphosphate (SS) fertilizer associated with inoculation with microorganisms. The experiment was carried out in a greenhouse with corn as a test plant, evaluated up to 35 days after emergence. The treatments consisted of full sources (100%) of SS and PR applied separately, and the control (without P source), in addition to balanced combinations, where reducing SS increased PR, so that in the end all treatments received 80 kg ha-1 of P2O5, however, from different sources. All treatments with phosphate sources were also tested with three inoculants, Ceratobasidium sp., Tulasnella sp. and a Bacillus mix: Bacillus megaterium + Bacillus subtilis. Phytometric parameters of maize were evaluated, and chemical and microbiological attributes in the soil. The doses of carbonatite combined with the reduced doses of SS statistically and positively affected the corn performance. The combinations of 75% SS + 25% carbonatite and 50% of both, proved to be more efficient to maintain the initial development of corn, compared to the full dose of SS (conventional fertilization), and increments of up to 87% compared to them with the control. All inoculants, when applied without phosphate fertilization, were efficient to maintain the initial development of cor. The carbonatite rock powder does not present benefits when applied alone, needing to combine it with other more soluble sources of P for the corn crop.